(untitled) (Brazilian Geographical Journal, 2017)
Appreciation of natural spaces in our society began in the Modern Age, but was inserted in the symbolic idea of nature, something external to the human, therefore, dicothomous. Say that we conserve to contribute for the ecological balance or for the own intrinsic value of biodiversity is partial and perhaps naive. Appreciation of the biodiversity and consequently of the protected areas in the world has much reason in the world economy. In the midst of this discussion are the indigenous and traditional communities, which have different perceptions and values of Nature. Thus, we sought to discuss about the term environmental conservation and its relationship with the indigenous and traditional communities. And on the other hand, seek to understand what conservation is for these communities. For this, the methodology was based on literature review. It is expected to bring geographic reflections to the world thematic, which has Brazil as the main subject in this process.